Afrocentric Framework for Family Business Succession: Exploring the Role of Business Backgrounds as Moderators - Dzvairo, Abraham; Taft, Trevor (Journal of Business and Management Review, 2024)
Research Aims: The research is motivated by the significance of ensuring a successful leadership succession planning process in family-owned businesses in Sub-Saharan Africa. This study aims to determine the moderating effect of the family business leader’s background variables on family business succession planning success and family business survival and develop a framework for FOB succession planning. Design/Methodology/Approach: The population of the study were family businesses in the cities of Mutare and Harare in Zimbabwe, amounting to 480 accessed from Small to Medium Enterprises (SME) databases in the cities.  Based on the Yamane formula with a margin of error of 5%, a sample of 218 family business leaders was obtained using a simple random sampling technique. The research method for this study was a survey method following a quantitative approach. The study used a questionnaire as a data collection instrument. Descriptive data analysis, correlations analysis, and regression analysis were used as data analysis techniques. Research Findings: The results of this study showed that the utilisation of Ubuntu and successor development and selection have a positive significant relationship with family business succession planning success. The education level of the business leader and the business age moderate the relationship between the utilisation of Ubuntu and the FOB succession planning process as well as the relationship between successor development and selection and the perceived success of the succession planning process. Theoretical Contribution/Originality: This research contributes to literature on family business succession planning variables and provides a framework for leadership succession planning in family businesses. Keywords: Afrocentric, family business, leadership, succession planning, moderation.